Ocimum gratissimum Linn. Reverses Cadmium-induced Toxicity of Spermatic Parameters of the Male Guineapig (Journal of Experimental and Clinical Anatomy, 2024)
The influence of the aqueous crude extracts of Ocimum gratissimum Linn. leaf on cadmium (Cd)-induced toxic effects on spermatic parameters of the male guineapig (GP) was investigated. In n=5, Cd (0-8mg/kg) caused a dose-dependent inhibition or reduction of various spermatogenic parameters namely - number of normal sperm cells: 55.75±2.02 ×106 to 7.50±1.19 ×106 /ml; number of abnormal sperm cells: 2.25±0.25 ×106 to 8.25±2.18 ×106 /ml and total sperm count: 58.00±1.96 ×106 to 15.75±2.63 × 106 /ml; motility: 64.25±2.39 % to 26.50±1.71%; morphology: 5.75±0.75 % to 38.25±2.72 %; and a significant increase (P<0.05) in particulate and primordial sperm cell counts in the male GP. However, injection of Ocimum gratissimum Linn. extract after Cd administration had little or no significant effect on the above-mentioned parameters. Pretreatment with 5mg of O. gratissimum, with subsequent administration of cadmium, blocked or reversed the Cd-induced toxicities on the various spermatogenic parameters- motility:26.50±1.71% to 53.25±2.14%; morphology: 38.25±2.72% to 8.75±1.25%; number of normal sperm cells: 7.50±1.19 ×106 to 27.25±1.60 ×106 /ml; number of abnormal sperm cells: 8.25±2.18 ×106 to 5.25±0.63 ×106 /ml and total sperm count: 15.75±2.63×106 to 32.50±1.85 ×106 /ml. The observed influence of O. gratissimum on Cd-induced toxicity may be the consequence of the antioxidant action of the plant extract on the spermatogenic apparatus of the organism.